Crianças e o CAPSI : do imperativo ao hiperativo. qual o tratamento? - Andrade, Luiz Felipe Oliveira de (2014)
It is evident nowadays the over-diagnosis of hyperactivity. Our survey in CAPSi (Center of Psychosocial Care of Children and Adolescents ) found the using of "imperative " or "imperative child " to name these children . The hyperactive functioning can be elucidated by psychoanalysis reading which highlights the various levels at which the imperative reaches the subject. This can be done by the adherence to the sub - line search: Limits, boundaries and addressments between mother and child of Nanette Zmeri Frej. As the Freudian Aufhebung movement presented by Frej (2003), the first boundary will structure the self as distinct from the object and the functions of Attention and Motricity (axes in the diagnosis of hyperactivity disorder). Another limit to this movement can be situated on the Oedipus Complex that interdicts the incest and regulates human relationships. This limit will also have influence on Attenction, Mobility and above all on the conduct, which could be transgressive. (Another diagnosis axe). These considerations have approached us the way professionals understand the CAPSi, a hyperactive child and its treatment. This approach was also possible through semi-structured interviews to professionals who work with children diagnosed asking these professionals about their concept about the problem and how they treat them.We found that hyperactivity of children deal with the problems of the first boundaries that distinguish the self from the external world and self-other as seen in the absence of addressment, since " they don t stop " and many of the hyperactivity and conduct disorders represent conflicts of children and adolescents with Oedipal Law, exemplified in the statements reported by professionals: " Teach me to be quiet ! " "to be obedient! " We identify in one hand the disciplinary interventions, expressed in "setting limits" to the children and on the other hand the CAPSi´s staff attempting to account for the constitutive limits of children, making a subject hypothesis to them and also considering their addressments to their Other. Finally, we note how important is the CAPSi not be guided through imperatives of productivity up to the point of forgetting the limits of their interventions and the need of interdisciplinary and territory networking performance otherwise the CAPSi could become hyperactive itself.